2014
DOI: 10.14310/horm.2002.1524
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of MC4R and FTO risk alleles on childhood obesity in Greece

Abstract: 2015, 14(1):126-133 Address for correspondence: Christina Kanaka-Gantenbein, MD, PhD, Associate Professor for Paediatrics Endocrinology-Juvenile Diabetes, First Department of Paediatrics, University of Athens Medical School, "Agia Sophia" Children's Hospital, Thivon & Livadias Str., GR 11527, Goudi, Athens, Greece, E-mail: chriskan@med.uoa.gr Received: 02-03-201402-03- , Accepted: 18-06-2014 Research paper epidemic. It has been estimated that in 2010, 43 million children aged <5 years were overweight or obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 41 publications
5
12
1
6
Order By: Relevance
“…The C/C genotype was significantly more frequent among individuals with higher BMI and WHtR values. This confirms the relationship between MC4R rs17782313 and obesity risk reviewed by Xi et al and evidenced by Lazopoulou in a European population of children . Despite the low MAF at PPARG rs1801282 and the previous contradictory results about its relationship with obesity , the PPARG G/G genotype resulted to be significantly associated with body overweight in our sample, confirming the results obtained in another young European population by Ochoa et al .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The C/C genotype was significantly more frequent among individuals with higher BMI and WHtR values. This confirms the relationship between MC4R rs17782313 and obesity risk reviewed by Xi et al and evidenced by Lazopoulou in a European population of children . Despite the low MAF at PPARG rs1801282 and the previous contradictory results about its relationship with obesity , the PPARG G/G genotype resulted to be significantly associated with body overweight in our sample, confirming the results obtained in another young European population by Ochoa et al .…”
Section: Discussionsupporting
confidence: 92%
“…Even if a possible interaction among ACE , MC4R , FTO and PPARG genes can be inferred by GWASs, which supported their relation with obesity and overweight, previous investigations did not test the presence of synergistic effects using a targeted approach. However, it should be mentioned that several studies have been conducted on this topic; a longitudinal study from Bouwman et al reported that adult men carrying FTO rs9939609 T/T genotype + ACE rs4646994‐D allele were protected against weight gain over a 10‐year period; Lazopoulou et al showed a cumulative effect of the presence of FTO rs9939609‐A allele and MC4R rs17782313‐C allele on childhood obesity in a Greek population; Goni et al showed that carrying unfavorable genotypes at both FTO rs9939609 and MC4R rs17782313 loci can influence weight loss in response to a hypocaloric diet; Carlos et al failed to prove the interaction of FTO rs9939609 and PPARG rs1801282 with obesity in Portuguese women; Passaro et al demonstrated a gene–gene interaction between PPARG rs1801282 and ACE rs4646994 on BMI and fat mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies showed that the risk allele A of rs9939609 in FTO gene was associated with increase of the BMI and incidence of obesity (11)(12)(13) . The presence of both risk alleles A and C from rs9939609 in FTO gene and rs17782313 in MC4R gene respectively caused 4-fold increase of obesity risk in childhood and adolescents from Greece origin (14) . Luczyoski et al (15) showed that the main factors that caused an increase of BMI in children with Type 1 Diabetes, especially in female gender, are poor metabolic control and carrying the A allele of the rs9939609.…”
Section: Introductionmentioning
confidence: 99%